An experimental investigation on the correlation between the aggregate size effect and the structural size effect. (July 2020) - Zhu, Ran; Alam, Syed Yasir; Loukili, Ahmed
Highlights: Size effect is investigated for three concretes where aggregate size is scaled. Complete aggregate grading curve is scaled with the same scaling factor. The identical size effect curve is obtained while scaling the aggregate size. Relationship between fracture energy and aggregate size is established. Relationship between fracture length parameters and aggregate size is established. Role of aggregate size and specimen size on the overall brittleness of the structure is established. Abstract: Concrete failure properties are significantly affected when the size of the structure changes. This size effect which is due to the presence of fracture process zone led by the aggregate size, has been studied in the literature only for a given concrete, however, the role of aggregate size on the size effect parameters is not clear. This paper presents an original experimental study where both the characteristic structural dimension ( D ) and the aggregate size ( d ) are considered as the scaling factors. The size effect is investigated by scaling of the characteristic structural dimension ( D ) on three concretes, where the aggregate size ( d ) is scaled with the same factor. In these concretes, the mortar content, the water/cement ratio and the aggregate content are kept as constant. While scaling the aggregate size ( d ), not just the maximum aggregate size is scaled but the complete grading curve is scaled with the same factor, which has never been done in the literature. This precise scaling of each fraction of the aggregate content in concrete and the scaling of structural dimensions reveal a direct correlation between aggregate size effect and the structural size effect parameters.